Stress tests and information disclosure: An experimental analysis - Cox, Caleb; Davis, Douglas; Korenok, Oleg; Lightle, John (Journal of Banking & Finance, 2023)
To improve the stability of the banking system the Dodd-Frank Act mandates that central banks conduct periodic evaluations of banks’ financial conditions. An intensely debated aspect of these ‘stress tests’ regards how much of that information generated by stress tests should be disclosed to financial markets. This paper uses an environment constructed from a model by Goldstein and Leitner (2018) to gain some behavioral insight into the policy tradeoffs associated with disclosure. Experimental results indicate that variations in disclosure conditions are sensitive to overbidding for bank assets. Absent overbidding, however, optimal disclosure robustly improves risk sharing even when banks behave non-optimally.